Moving towards a multidimensional dynamic approach to nature and health: A bioavailability perspective. Issue 1 (3rd October 2021) - Sumner, Rachel C.; Cassarino, Marica; Dockray, Samantha; Setti, Annalisa; Crone, Diane M.
Abstract: The benefits of exposure to nature for health and well‐being have been demonstrated across multiple disciplines. Recent work has sought to establish one 'dose' or type of nature exposure that is universally beneficial, which has proven difficult. We use the principles of psychopharmacology to look beyond the use of dose as a concept for prescribing nature. Instead, we posit a multidimensional model of bioavailability of nature to shift the focus beyond universal effects, and instead consider the relationship between health and nature as dynamic, changeable and heavily contextual. We propose that the bioavailability of nature interactions is constructed through understanding route of administration, dose and concentration. By delineating the mechanisms of health benefit derived from the type of behavioural interaction (through being, doing and living), the route of administration of nature interactions may be highly variable not just between, but also within, individuals. We propose concentration as being a meeting between the subjective aspects of the individual and the subjective qualities of the nature at that specific time and place. We use a 'green equation', for mapping the processes and pathways that belie the interaction between the person and their environment. Here, the nature/health association as a dynamic interaction, and we operationalise this within a multidimensional construct of bioavailability. We provide an overview of this testable model and summarise with preliminary evidence as well as a research agenda for the future. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.